Genome-wide association study of circulating interleukin 6 levels identifies novel loci. Issue 5 (30th January 2021) - Ahluwalia, Tarunveer S; Prins, Bram P; Abdollahi, Mohammadreza; Armstrong, Nicola J; Aslibekyan, Stella; Bain, Lisa; Jefferis, Barbara; Baumert, Jens; Beekman, Marian; Ben-Shlomo, Yoav; Bis, Joshua C; Mitchell, Braxton D; et al.
Abstract: Interleukin 6 (IL-6) is a multifunctional cytokine with both pro- and anti-inflammatory properties with a heritability estimate of up to 61%. The circulating levels of IL-6 in blood have been associated with an increased risk of complex disease pathogenesis. We conducted a two-staged, discovery and replication meta genome-wide association study (GWAS) of circulating serum IL-6 levels comprising up to 67 428 ( n discovery = 52 654 and n replication = 14 774) individuals of European ancestry. The inverse variance fixed effects based discovery meta-analysis, followed by replication led to the identification of two independent loci, IL1F10/IL1RN rs6734238 on chromosome (Chr) 2q14, ( P combined = 1.8 × 10 −11 ), HLA-DRB1/DRB5 rs660895 on Chr6p21 ( P combined = 1.5 × 10 −10 ) in the combined meta-analyses of all samples. We also replicated the IL6R rs4537545 locus on Chr1q21 ( P combined = 1.2 × 10 −122 ). Our study identifies novel loci for circulating IL-6 levels uncovering new immunological and inflammatory pathways that may influence IL-6 pathobiology.